Do Stability of Care and Teacher–Child Interaction Quality Predict Child Outcomes in Early Head Start?. Issue 3 (3rd April 2019) - Choi, Ji Young; Horm, Diane; Jeon, Shinyoung; Ryu, Dahyung
ABSTRACT: Research Findings : This study examined whether children's outcomes at age 3 were predicted by their experiences in Early Head Start (EHS), focusing on 2 key features of infant and toddler care: (a) stability of care and (b) teacher–child interactions. This study further explored potential interaction effects between stability of care and teacher–child interactions in predicting child outcomes. Three main results were found from secondary analyses of the recently released EHS longitudinal data set the EHS Family and Child Experiences Study (Vogel & Boller, 2009–2012). First, children who had stability of care (no teacher change) were rated as having fewer behavior problems and higher social competence. Second, children were rated as demonstrating better orientation/engagement and emotional regulation when they were in EHS classrooms observed to have higher emotional and behavioral support. Third, teacher–child interactions that are emotionally and behaviorally supportive may mitigate the potential drawbacks of experiencing instability of care on early social-emotional development. Study implications are discussed. Practice or Policy : Both stability and quality teacher–child interactions are important in center-based infant and toddler care, and ensuring quality teacher–child interactions is particularly important for children who experience teacher changes during their infant and toddler years.